Public policies on urban mobility and practices to project prioritization: A multi-criterial approach (Research, Society and Development, 2021)
The work aimed at structuring a multicriteria decision support model for choosing priority projects that materialize public policies on urban mobility through the Analytic Hierarchy Process method. The influential factors of the decision-making process were chosen with the public experts in the mobility area of three cities in the State of São Paulo. The relative importance of the factors was were assigned by means of judgments by public and academic experts. The determining factor "Origin of demand" was the most important and, in this group, the influential factor "urban policy" stands out, which consists of projects foreseen in the Master Plan or in the Urban Mobility Plan. The model was validated through its application to prioritize two projects in Lorena city. The study contributes to mobility planning by proposing the model and provides a decision support tool to guide the execution of mobility projects.